Photodegradation of pharmaceuticals studied with UV irradiation and differential scanning calorimetry - Menard, Kevin; Brostow, Witold; Menard, Noah (Publishing House of Lviv Polytechnic National University, 2011)
Given rapidly increasing concerns about photodegradation of pharmaceuticals, we have applied accurate methods to quantitatively evaluate the drug photostability. The drugs studied were nifedrine, acetylsalicylic acid, acetaminophen, cetirizine, and pantoprazole. UV energy striking a target has been determined by using graphite. Runs were performed by placing each sample in a pan with a quartz lid and exposing it to ultraviolet (UV) light for periods of time ranging from 1 to 120 seconds. Percentage decomposition as a function of time has been determined for each pharmaceutical. Fast differential scanning calorimetry (DSC) in situ was used to evaluate changes in thermophysical behavior of the drugs and possible formation of new phases. The UV degradation rates so determined cover a very wide range, from 0.1 to 20.0 %/s. Factors affecting the photodegradability are discussed. Для кількісного оцінювання фотостабільності лікарських препаратів: ніфедрину, ацетилсаліцилової кислоти, парацетамолу, цетиризину і пантопразолу застосовано прецизійні методи аналізу. Опромінення ультрафіолетом вивчено протягом 1–120 с. Для кожного лікарського препарату досліджено залежність відсотку розкладу від часу опромінення. За допомогою диференціальної скануючої калориметрії (ДСК) оцінено зміни теплофізичних властивостей препаратів і можливість утворення нових фаз. Встановлено, що швидкість УФ-деградації коливається від 0,1%/с до 20,0%/с. Розглянуто чинники, що впливають на фотодеградацію.
Вивчення фотодеградації лікарських препаратів за допомогою УФ-опромінення і диференціальної скануючої калориметрії
Keywords: pharmaceutical photostability; UV irradiation; drug DSC analysis; photo-DSC; фармацевтична фотостабільність; УФ-опромінення; ДСК аналіз; фото-ДСК